Valine biosynthesis in Saccharomyces cerevisiae is regulated by the mitochondrial branched-chain amino acid aminotransferase Bat1 - Natthaporn Takpho; Daisuke Watanabe; Hiroshi Takagi (Microbial Cell)
In the yeast Saccharomyces cerevisiae, the branched-chain amino acid aminotransferases (BCATs) Bat1 and Bat2 catalyze the conversion of α-ketoisovalerate, α-keto-β-methylvalerate, and α-ketoisokaproate and into valine, isoleucine, and leucine, respectively, as the final step of branched-chain amino acid biosynthesis. Bat1 and Bat2 are homologous proteins that share 77% identity, but Bat1 localizes in the mitochondria and Bat2 in the cytosol. Based on our preliminary finding that only disruption of the BAT1 gene led to slow-growth phenotype, we hypothesized that Bat1 and Bat2 play distinct roles in valine biosynthesis and the regulation of cell growth. In this study, we found that intracellular valine content was dramatically decreased in Δbat1 cells, whereas Δbat2 cells exhibited no changes in the valine level. To further examine the distinct roles of Bat1 and Bat2, we constructed two artificial genes encoding the mitochondrial-targeting signal (MTS)-deleted Bat1 (Bat1-MTS) and the MTS of Bat1-fused Bat2 (Bat2+MTS). Interestingly, Bat2+MTS was relocalized into the mitochondria, because Bat2 localization was changed to the mitochondria by addition of MTS, and could partially restore the valine content and growth in Δbat1Δbat2 cells. These results suggest that the mitochondria are the major site of valine biosynthesis, and mitochondrial BCAT is important for valine biosynthesis in S. cerevisiae.